Randomized placebo-controlled trial of the effects of aspirin on dementia and cognitive decline. - Ryan, Joanne; Storey, Elsdon; Murray, Anne M; Woods, Robyn L; Wolfe, Rory; Reid, Christopher; Nelson, Mark R; Chong, Trevor TJ; Williamson, Jeff D; Ward, Stephanie A; Lockery, Jessica E; Orchard, Suzanne G; et al. (2020)
OBJECTIVE: To determine the effect of low-dose aspirin vs placebo on incident all-cause dementia, incident Alzheimer disease (AD), mild cognitive impairment (MCI), and cognitive decline in older individuals.